Implications of COVID-19 for resumption of sport in South Africa: a South African Sports Medicine Association (SASMA) position statement - Patricios, J.; Ramagole, A.; Zondi, P.; Pillay, L.; Viviers, P.; van Rensburg, D. C. J. (South African Journal of Sports Medicine, 2020)
The significant impact of the coronavirus disease 2019 (COVID-19) pandemic has extended to sport with the cessation of nearly all professional and non-professional events globally. Recreational parks and fitness centres have also closed. A challenge remains to get athletes back to participation in the safest way, balancing the protection of their health while curbing the societal transmission of the virus. With this Position Statement, the South African Sports Medicine Association (SASMA) aims to guide return-to-sport as safely as possible, in an evidence-based manner, given that COVID-19 is a new illness and new information from experts in various fields continues to emerge. Clinical considerations are briefly described, focusing on a return-to-sport strategy, including education, preparation of the environment, risk stratification of sports and participants, and the practical implementation of these guidelines. The management of the potentially exposed or infected athlete is further highlighted. It is important that persons charged with managing athletes` return-to-sport in any environment must be up-to-date with local and international trends, transmission rates, regulations and sport-specific rule changes that might develop as sport resumes. Additionally, such information should be applied in a sports-specific manner, considering individual athlete`s and team needs and be consistent with national legislation.